2007
DOI: 10.1111/j.2007.0018-0661.01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-2 affects lifespan and oxidative stress in Drosophila

Abstract: Thioredoxins are proteins that have thiol-reducing activity and a characteristic conserved active site (WCGPC). They have several documented functions, e.g. roles in defences against oxidative stress and as electron donors for ribonucleotide-reductase. In Drosophila melanogaster there are three "classical" thioredoxins with the conserved active site: deadhead, ThioredoxinT and Thioredoxin-2. Here, we report the creation of null-mutations in the Thioredoxin-2 (Trx-2) gene. Characterization of two Trx-2 mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Moreover, the trx-2;dhd and trx-2;trxT double mutants were similar in longevity to the trx-2 single-mutant flies. Using a P-element Trx-2 transgene, it was possible to not only rescue the longevity deficits for all of the mutants, but also to slightly extend the life span relative to the wild-type control under both normal conditions and under OS (exposure to paraquat) (112). Because only one transgenic line was used and because the randomness of transgene insertion in the genome can have a confounding effect, the results of these experiments should be regarded as tentative.…”
Section: Thioredoxinsmentioning
confidence: 99%
“…Moreover, the trx-2;dhd and trx-2;trxT double mutants were similar in longevity to the trx-2 single-mutant flies. Using a P-element Trx-2 transgene, it was possible to not only rescue the longevity deficits for all of the mutants, but also to slightly extend the life span relative to the wild-type control under both normal conditions and under OS (exposure to paraquat) (112). Because only one transgenic line was used and because the randomness of transgene insertion in the genome can have a confounding effect, the results of these experiments should be regarded as tentative.…”
Section: Thioredoxinsmentioning
confidence: 99%
“…The Trx-2 gene is located in region 30C on chromosome 2L, and the protein has been crystallized, in both reduced and oxidized forms (Wahl et al 2005), and characterized in vitro (Bauer et al 2002). In vivo, Trx-2 has been shown to have moderate effects on both life span and resistance to oxidative stress (Svensson and Larsson 2007). In contrast to Trx-2, both DHD and TrxT are sexspecific thioredoxins.…”
Section: Introductionmentioning
confidence: 99%
“…The important roles of Trx in oxidative stress and longevity have been well documented by studies with C. elegans and Drosophila [18,19]; however, the exact roles of Trx in aging and age-related diseases in mammals have not been fully explored. Thus, we previously conducted an aging study with Trx transgenic mice [Tg(act- TXN ) +/0 ] [20] and demonstrated that Trx overexpression showed resistance to oxidative stress, which was associated with an extension of only the earlier part of lifespan compared to WT littermates [20].…”
Section: Introductionmentioning
confidence: 99%